Musica ex Machina Machines thinking musically - Impett, Jonathan (Lausanne, CH EPFL, 2024)
From Medieval theory to modern AI, Musica ex Machina: Machines Thinking Musically explores the history of computational and algorithmic thought in music, showcasing how technological advances and human creativity have continuously expanded the boundaries of musical expression. Through historical objects, musical artworks, and immersive installations, the exhibition presents the works of past and present visionaries while looking ahead to the future of music.Major exhibition (50+ exhibits)
0
Major exhibition at EPFL Pavilions (50+ exhibits), Lausanne. 20/9/24-26/6/25
0
Keywords: Music, Thought and Technology